The SIMUS method addresses two important MCDM drawbacks: Getting different results for the same problem, and the inability to model complex scenarios - Nolberto Munier (Trends in Computer Science and Information Technology - Peertechz Publications, 2022)
This paper considers that actual methods for addressing MODM or MCDM scenarios share two shortcomings along these lines: a) Failing to show equal results when different MCDM methods solve the same problem. b) Inability to replicate actual scenarios, by not taking into account existing conditions, and thus, producing an approximate representation of reality, which obviously, renders not reliable results. This paper shows how the SIMUS method addresses these two shortcomings.